BUDGET PERFORMANCE OF BANK SAMPAH MALANG (BSM) : CURRENT REALITY AND FUTURE SUBJECT - Ridha Fauziah; Mardiyono .; Motoko Kawano (Universitas Tribhuwana Tunggadewi, 2015)
In reaction to the rapid increase of garbage, the Indonesian government has addressed the serious challenge of waste problems, and Malang Municipality local government established Malang Waste Bank (Bank Sampah Malang (BSM)) for the purpose of the implementation of reducing, reusing, and recycling (3Rs). The 3Rs are implemented by running a waste recycling business and encouraging people to separate their waste. This study aims to analyze the current reality of BSM activities and clarify its economic viability. In order to measure the economic viability of BSM, BSM’s budget performances were analyzed by using BSM’s financial statements, whereas the role of BSM as a social function is examined by analyzing the in-depth interviews, field observations, and secondary data. The results of the analysis show that BSM is not economically profitable. However, the existence of BSM should be maintained because it has many social benefits, such as changing people’s behavior toward waste, enhancing community participation in managing waste, and giving extra money to BSM’s members.